Perianal giant condyloma acuminata in an infant: an alarming lesion for a pediatric surgeon - Altınay-Kırlı, Elif; Güçer, Şafak; Karnak, İbrahim (The Turkish Journal of Pediatrics, 2011)
Condyloma acuminatum (CA), which is a large cauliflower-like tumor, has been linked to human papilloma virus (HPV) types associated with skin warts. It is an uncommon condition in children, and there is no consensus regarding the optimal treatment. HPV may be acquired via sexual transmission, vertical transmission or extragenital contact. We report herein a 1.5-year-old girl with perianal giant CA, which developed due to extragenital contact and consisted of HPV types 6 and 18, to emphasize the effectiveness of surgical excision.